Identification and Validation of a Major Quantitative Trait Locus for Adult Plant Resistance Against Leaf Rust From the Chinese Wheat Landrace Bai Qimai - Wang, Zhen; Jiang, Xu; Zhang, Yuzhu; Du, Ziyi; Feng, Jing; Quan, Wei; Ren, Junda; Che, Mingzhe; Zhang, Zhongjun (Frontiers in Plant Science, 2022)
Leaf rust caused by Puccinia triticina Eriks. (Pt) is a common disease of wheat worldwide. The Chinese wheat landrace Bai Qimai (BQM) has shown high resistance to leaf rust for a prolonged period of time; the infected leaves of BQM displayed high infection types, but they showed low disease severities at the adult plant stage. To find quantitative trait loci (QTL) for resistance to leaf rust, 186 recombinant inbred lines from the cross Nugaines × BQM were phenotyped for leaf rust response in multiple field environments under natural Pt infections and genotyped using the 90K wheat SNP chip and simple sequence repeat markers. A total of 2,397 polymorphic markers were used for QTL mapping, and a novel major QTL (QLr.cau-6DL) was detected on chromosome 6DL from BQM. The effectiveness of QLr.cau-6DL was validated using three additional wheat populations (RL6058 × BQM, Aikang58 × BQM, and Jimai22 × BQM). QLr.cau-6DL could significantly reduce leaf rust severity across all tested environments and different backgrounds, and its resistance was more effective than that of Lr34. Moreover, QLr.cau-6DL acted synergistically with Lr34 to confer strong resistance to leaf rust. We believe that QLr.cau-6DL should have high potential value in the breeding of wheat cultivars with leaf rust resistance.